The Narration Process in Eco’s Understanding Fiction and Reality - Bujar Hoxha (Nalans, 2023)
The present paper shall aim to demonstrate that a narration process is a semiotic tool, which, among other tasks, serves to execute a process of signification. My effort shall range from factual “stories” and “retold stories” to fictional ones. This is so because semiotics treats various “realities”, from which some may be realistically occurring, while others may represent imaginative “facts” invented by authors. One of the differences between the two, as Eco has also pointed out, is the factor of “time”, which is both semiotically and philosophically relevant. The purpose of this text is also to demonstrate that narration can be conceived of in multiple sorts of “times”, out of which only one we can physically live (above all, as one of the differences between artistic creation and real-time narration). A “fictive reality” relates to artistic creativities that are an object to their semiotic shaping and interpretation. In conclusion, one can state that interpretative semiotics is competent for this vision and relevant for the method’s future development.